Determination of pulp necrosis based on periapical digital radiography histogram and pulp histopathology - Khoironi, Emi; Firman, Ria Noerianingsih; A, Azhari; Oscandar, Fahmi (Universitas Padjadjaran, 2017)
Introduction: Radiographic examination is needed to determine the diagnosis of pulp necrosis in addition to a clinical examination. Visual observation was limited in seeing the colour change degree and hence an effort taken by assessing the histogram value. The purpose of this study was to obtain the pulp chamber histogram pattern which reveals its grey scale value, trend, intensity average, histogram variation, and histograms maximum regional of interest (ROI) through digital periapical radiograph. Methods: This study was a descriptive study of the total of nine pulp chamber periapical radiograph data samples. The samples were divided into three groups, the 1st group was the data taken prior to the tooth extraction, the 2nd group was the data collected after the teeth extraction, and the 3rd group was the data of priorly pulpless teeth. Results: There was a tendency of histogram graphic shifting to the left side, likely towards the radiolucent area on ROI of the pulp at the apical region, whilst histopathologically, a massive infiltration of a round PMN cells was found in the area. This finding supported the determination of pulp necrosis diagnose. Conclusion: The tooth with a pulp necrosis showed a tendency that led to radiolucency on periapical radiograph histogram, and histopathologic examination showed massive infiltration of a round PMN cells, thus supported the pulp necrosis diagnose.